Poro Point Special Economic and Freeport Zone Development Framework Planning Project final report - U.P. Planning and Development Research Foundation, Inc. (UP PLANADES). (Quezon City UP PLANADES, 2003)
Shows the strategic framework/structure plan for the western section of the Poro Point Special Economic and Freeport Zone (PPSEFZ) to guide succeeding detailed planning by developers.
CD-ROM
Keywords: Poro Point Special Economic and Freeport Zone